OPTIMIZATION OF MANGROVE UTILIZATION AS A FOOD RESOURCE AND STRENGTHENING THE ECONOMY OF COASTAL COMMUNITIES - Muh. Agus Salim; Lukman Hardia; Justitia Cahyani Fadli; Sitti Hadija Samual; Ica Damayanti; Mika Tri Kumala Swandari (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2026)
The coastal area of Klawalu Village possesses abundant mangrove ecosystem potential; however, its utilization by the community remains limited to ecological functions and has not been optimized as a source of food, health products, or economic improvement. This community service program aimed to enhance community knowledge and skills in mangrove utilization through education, training, and mentoring approaches based on multidisciplinary collaboration. The implementation methods included socialization on the benefits of mangroves, training on mangrove-based food product processing, education on the use of mangroves as natural health ingredients, and assistance in product marketing strategies to support the coastal community’s economy. The activities involved community groups, small and medium enterprises (SMEs), and village officials as primary partners. The results demonstrated an increase in community understanding regarding the potential of mangroves as a source of functional food and natural health ingredients, as well as improved skills in processing economically valuable mangrove-based products. In addition, this program encouraged greater public awareness of the importance of preserving mangrove ecosystems as sustainable natural resources. This community service initiative is expected to become a model for coastal community empowerment based on local potential that supports health, food security, and sustainable economic strengthening.